2003
DOI: 10.1038/sj.gt.3301880
|View full text |Cite
|
Sign up to set email alerts
|

Priming of T cells with aAd-transduced DC followed by expansion with peptide-pulsed DC significantly enhances the induction of tumor-specific CD8+ T cells: implications for an efficient vaccination strategy

Abstract: In recent years, vaccination strategies using antigen-presenting cells (APC) have been under investigation. Antigen delivery using genetic immunization through ex vivo transduction of dendritic cells (DC) is supposed to enhance the induction of antitumor responses in humans by activating a broad range of peptide-specific CD8 + T cells. In this study, we compared the potential of adenoviral (Ad)-transduced versus peptide-pulsed DC to induce melanoma-antigen (Ag)-specific T-cell responses in vitro. Whereas gp100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Using a DC cell line, Brossart et al (43) showed that DCs transfected with adenoviral vector or vaccinia virus expressing the SIINFEKL peptide induce stronger in vitro stimulation of CTL activity than peptide-pulsed DCs. In contrast, Tuettenberg et al (32) recently showed that adenoviral vector-transduced DCs only induced short-lived immune responses compared with Ag-pulsed DCs in vitro. The evidence suggests that the generation of vector-specific immune responses through repeated stimulation by adenoviral vector-transduced DCs may interfere with the development and potency of the desired Ag-specific T cell responses (32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a DC cell line, Brossart et al (43) showed that DCs transfected with adenoviral vector or vaccinia virus expressing the SIINFEKL peptide induce stronger in vitro stimulation of CTL activity than peptide-pulsed DCs. In contrast, Tuettenberg et al (32) recently showed that adenoviral vector-transduced DCs only induced short-lived immune responses compared with Ag-pulsed DCs in vitro. The evidence suggests that the generation of vector-specific immune responses through repeated stimulation by adenoviral vector-transduced DCs may interfere with the development and potency of the desired Ag-specific T cell responses (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tuettenberg et al (32) recently showed that adenoviral vector-transduced DCs only induced short-lived immune responses compared with Ag-pulsed DCs in vitro. The evidence suggests that the generation of vector-specific immune responses through repeated stimulation by adenoviral vector-transduced DCs may interfere with the development and potency of the desired Ag-specific T cell responses (32). Nonviral transfection of DCs would obviate this obstacle, and the delivery of Ag-encoding mRNA to DCs has been shown to result in Ag expression and stimulation of Ag-specific T cell responses (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supportive of our hypothesis are (i) recent reports for other oncolytic viruses, which have shown that their anti-tumor efficacy in part or even to a large extent is mediated by anti-tumor immunity rather than direct viral cell lysis [13][14][15][16][17] and (ii) the observation, in genetic vaccination studies using replication-deficient adenoviral vectors, that anti-viral immune activation has adjuvant activity for immunity to tumor antigens. 18 Importantly, strategies for transgene expression by oncolytic adenoviruses facilitate the modulation and potentiation of viral oncolysis-induced anti-tumor immune responses by expression of immunoregulatory factors. 4 The question as to whether potent anti-cancer immune responses are induced by adenoviral oncolysis has not been addressed adequately to date.…”
mentioning
confidence: 99%